Structural refinement, Raman spectroscopy, optical and electrical properties of (Ba1-xSrx)MoO4 ceramics - Ghosh, S. K.; Rout, S. K.; Tiwari, A.; Yadav, P.; Sczancoski, J. C. [UNESP]; Filho, M. G. R.; Cavalcante, L. S. (Springer, 2015)
In this paper, structural refinement, Raman spectroscopy, optical and electrical properties of barium strontium molybdate [(Ba1-x Sr (x) )MoO4] ceramics with different (x) contents (x = 0; 0.1; 0.2; 0.3; 0.4; 0.5; 0.6; 0.7; 0.8; 0.9; and 1) were synthesized by the solid state reaction method. These ceramics were structurally characterized by X-ray diffraction (XRD), Rietveld refinement, and micro-Raman spectroscopy. The shape of the grains for these ceramics was observed by means of scanning electron microscopy (SEM) images. The optical properties were investigated using ultraviolet-visible (UV-Vis) absorption spectroscopy and photoluminescence (PL) measurements. The dielectric and ferroelectric properties were analyzed by permittivity (epsilon(r)), loss tangent (tan delta) and polarization versus electric field (P-E) hysteresis loop. XRD patterns, Rietveld refinement, and micro-Raman spectra showed that all ceramics are monophasic with a scheelite-type tetragonal structure. A decreased of lattice parameters and unit cell volume was observed with the increase of Sr2+ ions into BaMoO4 lattice. Rietveld data were employed to model the [BaO8], [SrO8] and [MoO4] clusters in the tetragonal lattices. The SEM images indicate that increased x content promotes a decrease in the grain size and modifications in the shape. UV-Vis spectra indicated a decrease in the optical band gap values with an increase in x content in the (Ba1-x Sr (x) )MoO4 ceramics. PL emissions exhibit a non-linear behavior to increase or decrease with the increase of Sr2+ ions in the tetragonal lattices, when excited by a wavelength of 350 nm. The P-E decreases along with slim hysteresis loop towards higher Sr2+ ions concentration. These effects are correlated with decrease in lattice parameters and c/a ratio in this tetragonal lattice. The microwave dielectric constant and quality factor were measured using the method proposed by Hakki-Coleman. Temperature coefficient and quality factor of these materials were measured by vector network analyzer.